Effect of Feed Withdrawal on Growth Performance and Carcass Characteristics of Heat Stressed Broiler Chicken (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted to study the effect of feedwithdrawal at different ages during the hottest summer days on thegrowth performance and some carcass traits of broiler chicken. Onehundred thirty five male chicks at 14 days of age (DOA) with averagebody weight (375 g/bird) were randomly allotted to three treatments withthree replicates each. The treatments consisted of the control (no feedwithdrawal), early feed withdrawal (EFW) at the fourth week of age andlate feed withdrawal (LFW) at the fifth week of age. The treatments wereassigned to a completely randomized design. The experiment lasted forfive weeks having one week as a transitional period, and it was terminatedat 49 DOA. The feed withdrawal duration was two weeks for each group.Feed withdrawal was undertaken from 10:00 am till 7:00 pm. Feed intakeand live body weight were recorded weekly. Feed conversion ratio (FCR)and the cumulative mortality rate were calculated. Some physical andchemical analyses were carried out for some carcass parts (drumstick andthigh). The abdominal fat pad (AFP) was removed and weighed. TheLFW group significantly (P ≤ 0.05) consumed the highest amount of feed,whereas the EFW group consumed the least amount. The cumulativemortality rate was significantly (P ≤ 0.05) lower for LFW and EFW, andthe control group recorded the highest rate. At 49 DOA, live body weightwas significantly (P ≤ 0.05) the highest for the LFW group, whereas theother groups recorded similar body weights. The overall FCR wassignificantly (P ≤ 0.05) the best for LFW group, whereas the control had
Keywords: Broiler; heat stress; feed withdrawal; eed withdrawa; feed consumption and conversion.